Capturing the Present in Northwestern Europe (1348-1648). A Cultural History of Present Before the Age of Presentism - (:unkn) unknown (My University, 2025)
This research examines how the concept of the present was perceived and experienced in Northwestern Europe during the period from the Middle Ages to the early modern era. This area, including the Netherlands, West Germany, Northern France, and Southern England, experienced significant shifts in politics, economy, religion, and art. With its diverse political systems, multiple languages, urban development, and evolving lifestyles, this region provides a unique historical backdrop, differing from the conventional Renaissance narrative. Our study is comprehensive and multidisciplinary, encompassing history, art, literature, linguistics, media studies, anthropology, and political science. We focus on three principal themes: tracing the evolution of the concept of the 'present' from 1348 to 1648; uncovering the unique cultural characteristics of Northwestern Europe; and exploring how individuals and their communities perceived and adapted to the notion of the present. Our analysis will investigate how discourses and visual media give shape to individual and collective perceptions of one's own time, how events are represented and interpreted, and how people responded to novel ideas and political and societal changes. The objective is to redirect historical focus towards Northwestern Europe, highlighting its complex diversity and critical role in influencing our comprehension of the present in a broader European context.
Keywords: Time; Present; Presentism; Middle Ages; Early Modern Times; Event; Current Events; Innovation; Northern Europe